Maternal and perinatal factors associated with subsequent meningococcal, Haemophilus or enteroviral meningitis in children: database study. - Goldacre, M; Wotton, C; Maisonneuve, J (2014)
We used a database of 248 659 births, with follow-up to subsequent disease, in the Oxford record linkage archive (1979-1999) to study the influence of family, maternal, and perinatal factors on subsequent hospital admission for meningococcal, Haemophilus, and enteroviral meningitis in the children. In this summary, we report key findings that were significant in multivariate analysis. Meningococcal meningitis was significantly associated with maternal smoking [odds ratio (OR) 2·1, 95% confidence interval (CI) 1·2-3·7]. Haemophilus meningitis was associated with having older siblings (e.g. second child compared to first-born, OR 3·3, 95% CI 2·0-5·6). Enteroviral meningitis was associated with low birth weight (OR 2·2, 95% CI 1·3-3·6) and male sex (OR 1·7, 95% CI 1·2-2·3). The mothers of six of the 312 children with enteroviral meningitis had previously had enteroviral meningitis themselves. We concluded that several maternal characteristics influence the risk of these types of meningitis.